Development of a Sustainable Supply Chain Network for Microfluidic Devices Made from Recycled Materials - Krystal Faith B. Javier; Butch G. Bataller; Maria Victoria Migo-Sumagang (Chemical Engineering Transactions)
Meeting the global diagnostic and monitoring demand has been a challenge, especially in places with limited laboratory facilities. To address this, microfluidic devices have been integrated into the diagnostic framework. Due to the nature of their usage, however, microfluidic devices for diagnosis and monitoring should be single-use and disposable. Since these devices are commonly made from thermoplastics derived from unrecyclable and/or nonrenewable sources, their production, use, and disposal are accompanied by a high carbon footprint. Using a Design for Sustainability approach, this work presents an optimization model for the development of a supply chain network that considers both the economic and the carbon footprint as objectives. The model is demonstrated using data derived from literature and the industry. Results of the analysis indicate that the entire polymer feed required for the hypothetical manufacturing plant can be composed solely of recycled polyethylene terephthalate regardless of which optimization parameter was prioritized. The models developed in the study reveal that production of the microfluidic device using recycled polyethylene terephthalate is accompanied by 0.13 kg CO2-eq/d per unit of product when carbon footprint is prioritized. This amount of emission also corresponds to a cost per unit of product of 0.0546 $/d when the minimization of the cost objective is prioritized. This proves that the use of recycled polymers can be a way to reduce the dependence of the microfluidics industry on unsustainable materials.